Syiar Dalam Alunan Syair: Nasyid Seni Dakwah Islam di Bandung Tahun 1990-2004 - Mardiani, Reni (Al-Isnad: Journal of Islamic Civilization History and Humanities, 2021)
This research explains the art of nasyid music as an art of Islamic dakwah in Bandung from 1990 to 2004, which was initially introduced as a chant to give speeches for Islamic student activists along with the spirit of defending Palestine and Afghanistan. This research uses historical method, namely topic choice, heuristics, source criticism, interpretation and historiography. The results of this study show that in its development nasyid is considered an art of music to offer resistance to Western music which affects young people, especially in urban areas. Nasyid has become a modern Islamic music which has become one of the alternative music streams to convey Islamic preaching in addition to the art of entertainment, so that nasyid has become an influential dakwah art for the people of Bandung, especially young people, many of whom are more familiar with Islam until they migrate. In 2004 nasyid in Bandung experienced ups and downs in which nasyid became a national festival, but nasyid began to be neglected due to the existence of popular Indonesian musicians who began releasing religious albums.